5-HT7 receptors in Alzheimer's disease. (November 2021) - Solas, Maite; Van Dam, Debby; Janssens, Jana; Ocariz, U.; Vermeiren, Yannick; De Deyn, Peter Paul; Ramirez, Maria J.
Abstract: Even though the involvement of serotonin (5-hydroxytryptamine; 5-HT) and its receptors in Alzheimer's disease (AD) is widely accepted, data on the expression and the role of 5-HT7 receptors in AD is relatively limited. Therefore, the objective of the present work was to study the expression of serotonergic 5-HT7 receptors in postmortem samples of AD brains and correlate it with neurotransmitter levels, cognition and behavior. The study population consisted of clinically well-characterized and neuropathologically confirmed AD patients (n = 42) and age-matched control subjects (n = 18). Reverse-transcription quantitative polymerase chain reaction (RT-qPCR) and high-performance liquid chromatography were performed on Brodmann area (BA) 7, BA10, BA22, BA24, hippocampus, amygdala, thalamus and cerebellum to measure mRNA levels of 5-HT7 receptors ( HTR7 ), as well as the concentrations of various monoamine neurotransmitters and their metabolites. Decreased levels of HTR7 mRNA were observed in BA10. A significant association was observed between HTR7 levels in BA10 and BEHAVE-AD cluster B (hallucinations) (rs(28) = 0.444, P  < 0.05). In addition, a negative correlation was observed between HTR7 levels in BA10 and both MHPG concentrations in this brain region (rs(45) = -0.311; P  < 0.05), and DOPAC levels in the amygdala (rs(42) = -0.311; P  < 0.05). Quite surprisingly, no association was found between HTR7 levels and cognitive status. Altogether, this study supports the notion of the involvement of 5-HT7 receptors in psychotic symptoms in AD, suggesting the interest of testing antagonist acting at this receptor to specifically treat psychotic symptoms in this illness. Highlights: Decreased levels of HTR7 mRNA were observed in BA10 of AD. A significant association was observed between HTR7 levels in BA10 and hallucinations. No association was found between HTR7 levels and cognitive status. HT7 antagonist may be of potential utility in treatment of psychotic symptoms in AD.